SAT0271 Development of a Novel SI Joint CT Score for Diagnosis of Axial Spondylitis. (9th June 2015) - Chan, J.; Sari, I.; Salonen, D.; Haroon, N.; Inman, R.D.
Abstract : Background: Imaging plays a fundamental role in the diagnosis of ankylosing spondylitis (AS); however, the diagnosis of AS is based on pelvic radiographs plagued by poor sensitivity, specificity, and reproducibility. Many AS patients, particularly those with inflammatory bowel disease (IBD), may have CT scans performed for other clinical indications and sacroiliitis may be incidentally noted. Previous studies have used a radiologist's adaptation of the modified New York Criteria (mNYC) as a gold standard for diagnosing sacroiliitis. Adaptation of the mNYC has not been validated in CT imaging. Objectives: To develop a validated scoring system for sacroiliitis on CT that can ground future studies in prevalence and pathogenesis. Methods: An expert panel consisting of 6 rheumatologists and one radiologist designed a preliminary scoring system of coronal images on CT with assessment of SI joint changes including sclerosis, erosions and ankylosis. 46 mNYC+ AS patients with CT scans of the abdomen/pelvis were identified and matched to 46 controls by age and gender that received CT scans for other indications but had no history of spondylitis, colitis, uveitis, or psoriasis. An initial training exercise involving 10 CT scans (5 AS patients and 5 controls) was conducted to optimize reliability and feasibility. In a subsequent exercise on 12 patients (6 AS and 6 controls), 2 readers separately read the CT scans blinded to clinical data to determine which features would best correlate with AS. Finally, 2 blinded readers performed a validation study on 68 CT scans (34 AS and 34 controls). Each patient's SI joints were divided into left and right as well as iliac and sacral segments for a total for 4 segments. The maximum number of erosions seen on a single slice was counted in each segment. Sclerosis was only measured on the slice with the longest synovial length. Sensitivity, specificity, and likelihood ratios were calculated for variables that correlated with AS. Combinations of variables were trialed to maximize sensitivity and specificity. Results: Features that significantly correlated with AS included ankylosis, presence of erosions, number of erosions, iliac sclerosis >0.5cm, and sacral sclerosis >0.3cm. Sclerosis was defined as any iliac sclerosis >0.5cm or sacral sclerosis >0.3cm in depth and >1cm in length. Inter reader reliability for these variables were 1.0 for ankylosis, 0.634 for iliac erosions, 0.548 for sacral erosions, 0.989 for number of iliac erosions, 0.995 for number of sacral erosions, 0.582 for iliac sclerosis, and 0.385 for sacral sclerosis. Fig 1A demonstrates the ROC curves for ankylosis, sclerosis, and erosions independently. When the total number of erosions seen on 1 slice for each individual segment was added, a score of ≥3 erosions was found to have the highest sensitivity and specificity for AS. Fig 1B demonstrates the ROC curves for combinations of ankylosis, sclerosis, and erosions for diagnosing AS. Conclusions: The presence of >1cm of ankylosis or ≥3 total erosions provided the highest sensitivity of 91% and specificity of 91%. The addition of >0.5cm of iliac sclerosis or >0.3cm of sacral sclerosis marginally increased the sensitivity to 94% but decreased specificity to 86%. On CT scan of the SI joints, the presence of ankylosis >1cm or ≥3 total erosions has the greatest diagnostic utility for AS. Disclosure of Interest: None declared